The False Promise of Elections on the Internet. - HEENEY, MATTHEW (Quadrant Magazine, 2014)
The article focuses on issues about a paper released by the Australian Electoral Commission (AEC) on internet voting at the request of the Electoral Council of Australia and New Zealand. The author provides his insights about AEC's internet voting as well as the risks associated with the proposed policy. Other issues related to internet-based voting mechanism are highlighted.